Human MAIT cell response profiles biased toward IL-17 or IL-10 are distinct effector states directed by the cytokine milieu - Caroline Boulouis; Elli Mouchtaridi; Thomas R. Müller; Jeffrey Y. W. Mak; David P. Fairlie; Peter Bergman; Jakob Michaëlsson; Jonas Halfvarson; Jenny Mjösberg; Marcus Buggert; Johan K. Sandberg (Proceedings of the National Academy of Sciences, 2025)
Mucosal-associated invariant T (MAIT) cells are unconventional T cells that mediate rapid antimicrobial immune responses to antigens derived from microbial riboflavin pathway metabolites presented by the evolutionarily conserved MR1 molecules. MAIT cells represent a large pre-expanded T cell subset in humans and are involved in both protective immunity and inflammatory immunopathology. However, what controls the functional heterogeneity of human MAIT cell responses is still largely unclear. Here, combining functional and transcriptomic analyses, we investigate how MAIT cell response programs are influenced by the cytokine milieu at the time of antigen recognition. Activation by MR1-presented antigen together with IL-12 induces intermediate levels of IFNγ and TNF, as well as a regulatory profile with substantial IL-10 production and elevated expression of TIM-3, LAG-3, and PD-1. Activation by the combination of antigen and IL-12 induces a c-MAF-dependent program required for IL-10 production. The MAIT cell-derived IL-10 mediates both autocrine and paracrine immune regulation. In contrast, coactivation of MAIT cells with IL-18 induces IL-17, GM-CSF, IFNγ, and TNF, without IL-10. Notably, IL-18 dominantly counteracts IL-10 expression. The activation states biased toward IL-10 or IL-17 production are reversible and do not represent stable subsets. Finally, MR1-restricted TCR-mediated activation without cytokine coactivation drives primarily granzyme B cytolytic arming. Altogether, these findings demonstrate that human MAIT cells adapt their functional effector response during antigen recognition to cytokine cues in the microenvironment, and identify programs biased toward either regulatory c-MAF-dependent IL-10 expression, or an inflammatory IL-17 and GM-CSF profile.